2021
DOI: 10.3390/ijerph18094570
|View full text |Cite
|
Sign up to set email alerts
|

How the Intensity of Night Shift Work Affects Breast Cancer Risk

Abstract: Background—In 2019, the IARC concluded that “night shift work is probably carcinogenic to humans (Group 2A), based on limited evidence from human epidemiological studies and sufficient evidence of cancer and strong mechanistic evidence in experimental Animals.” The negative health consequences of night shift work may depend on how the night shifts are scheduled. The aim of this study was to investigate how the characteristics of night work affect the risk of developing breast cancer. Methods—A case–control stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 35 publications
(51 reference statements)
1
12
0
10
Order By: Relevance
“…The observed trend of increased risk by longer exposure to night shift work is supported by earlier studies,2 but with some exceptions 7 21. Case–control studies with much more detailed exposure indicators than available in the cohort studies show generally more positive trends in the association of longer duration of night shifts and risk of breast cancer (eg, refs 19 22 23).…”
Section: Discussionsupporting
confidence: 54%
“…The observed trend of increased risk by longer exposure to night shift work is supported by earlier studies,2 but with some exceptions 7 21. Case–control studies with much more detailed exposure indicators than available in the cohort studies show generally more positive trends in the association of longer duration of night shifts and risk of breast cancer (eg, refs 19 22 23).…”
Section: Discussionsupporting
confidence: 54%
“…The jet lag protocol used here mimics the effects of rotating shift work or frequent eastbound trans-meridian flights and has been previously shown to cause severe perturbations of circadian rhythmicity ( 6, 7, 9 ). A recent epidemiological study showed that night shift work affects the risk of developing breast cancer by 2.34 times ( 53 ). Consistent with the results of published studies ( 7 ), we found that CRD affected the rhythmicity of many clock genes (e.g., Clock, Bmal1, Per1 , and Cry1 ) in the mammary glands; however, Per2 expression remained rhythmic after CRD, indicating that Per2 is more sensitive to phase entrainment signals of molecular oscillators in peripheral tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Younger workers have fewer chronic diseases, can recover from illness and injury earlier, and are more likely to have absences due to minor health problems or motivational issues compared with older workers 33 . In terms of the night shift, shift work negatively affects an employee's health and can increase the risk of cardiovascular diseases, gastrointestinal disorders, and cancer 35–37 . It was suggested that the intensity or the number of consecutive night shifts was a risk factor for a long‐term SA, 38,39 although detailed schedules of shift work were not included in this study, such as rotation types, the number of consecutive night shifts or intensity, and years of shift work.…”
Section: Discussionmentioning
confidence: 99%